Hybrid quantum mechanics/molecular mechanics studies of the active site of the blue copper proteins amicyanin and rusticyanin - Comba, Peter (Inorganica chimica acta, 2001)
The structures of the oxidized form of the two blue copper proteins amicyanin and rusticyanin, two cupredoxines with strikingly different properties, were analyzed with quantum mechanics/molecular mechanics (QM/MM). The minimum model for the QM part was evaluated with pure DFT calculations, and the strain imposed by the protein backbones on this structure is in the expected range, i.e., 74 kJ mol−1 for amicyanin and 82 kJ mol−1 for rusticyanin. The optimized structures are similar to the published X-ray crystal structures but the error on the experimental data is of the same order of magnitude as the variation between the two experimental structures and similar to the difference between the computed and experimental data.